New allelic variants found in key rice salt‐tolerance genes: an association study. Issue 1 (1st November 2012) - Negrão, Sónia; Cecília Almadanim, M.; Pires, Inês S.; Abreu, Isabel A.; Maroco, João; Courtois, Brigitte; Gregorio, Glenn B.; McNally, Kenneth L.; Margarida Oliveira, M.
Summary Salt stress is a complex physiological trait affecting plants by limiting growth and productivity. Rice, one of the most important food crops, is rated as salt‐sensitive. High‐throughput screening methods are required to exploit novel sources of genetic variation in rice and further improve salinity tolerance in breeding programmes. To search for genotypic differences related to salt stress, we genotyped 392 rice accessions by EcoTILLING. We targeted five key salt‐related genes involved in mechanisms such as Na+/K+ ratio equilibrium, signalling cascade and stress protection, and we found 40 new allelic variants in coding sequences. By performing association analyses using both general and mixed linear models, we identified 11 significant SNPs related to salinity. We further evaluated the putative consequences of these SNPs at the protein level using bioinformatic tools. Amongst the five nonsynonymous SNPs significantly associated with salt‐stress traits, we found a T67K mutation that may cause the destabilization of one transmembrane domain in OsHKT1;5, and a P140A alteration that significantly increases the probability of OsHKT1;5 phosphorylation. The K24E mutation can putatively affect SalT interaction with other proteins thus impacting its function. Our results have uncovered allelic variants affecting salinity tolerance that may be important in breeding.